PENERAPAN KARTU CERITA BERGAMBAR BERBASIS TEKS NARASI UNTUK MENINGKATKAN LITERASI MEMBACA PADA SISWA SD - Agustin, Nofelira; Febrianti, Reva; Adrias; Azmi Alwi, Nur (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Reading literacy for elementary school students is currently a focus in the learning process. Many students still have difficulty connecting the content of the reading material with what they read, especially narrative texts. This is caused by several factors, including low student interest in reading, lack of student engagement in class, and the lack of use of diverse learning media. One way to overcome this problem is to use learning media that is interesting and appropriate to student characteristics, such as the use of picture story cards in learning. This study aims to explain how the use of picture story cards can improve students' literacy skills in reading narrative texts. Using a qualitative approach and descriptive design, the research method is a literature study from various journals and sources relevant to the research topic. The data collection process includes analysis, comparison, and drawing conclusions from the results of previous studies on reading literacy, narrative texts, and visual learning media. The results show that picture story cards can increase students' interest in reading, help them understand the storyline, and help them connect the text content to real-world situations. In addition, it is proven that this media can make classes more active and enjoyable.